Early Added Sugars and Fructose Intake and Child Body Composition. (14th June 2022) - Fortin-Miller, Sara; Colombo, John; Carlson, Susan; Kerling, Elizabeth; Hull, Holly
Abstract: Objectives: Examine the associations between added sugars and fructose intake during the first 2 years of life and body composition in middle childhood. Our hypothesis is that infants and toddlers with higher added sugars and fructose intake will have greater percentage fat mass later in life compared to those with lower intakes. Methods: 24-hour dietary recalls were collected in children (n varied with age from 101 to 208) born to mothers who participated in the KUDOS study, a randomized control trial that evaluated the effect of prenatal DHA supplementation on offspring cognitive outcomes. Dietary data were reported from 6 weeks to 2y. Percentage fat mass (%fat) was measured by air displacement plethysmography (Bod Pod®) at 5, 7, 8, and 9y. Principal component analysis determined qualitative transitions of sugars intake across early childhood. Hierarchical linear regression models assessed the relationship between early added sugars and fructose intake and %fat later in life. Results: Clinical trial assignment did not affect outcomes. Added sugars and fructose intake increased over infancy and early childhood, starting at 31.5 and 0.04 grams/day at 6 weeks up to 44.8 and 17.9 grams/day by 2y for added sugars and fructose, respectively. Principal component analyses revealed two distinct phases of intake, with transitions at the end of the 1 st year, for both forms of sugar intake. Regressions were conducted for outcomes at each age, controlling for SES and average kcal intake during infancy. Added sugars intake during the 2 nd year had an unexpectedly negative association with %fat at 5y (b = −0.359, P < 0.01), while fructose intake during the 1 st year had a positive association with %fat at 8y (b = 0.361, P < 0.05). No other significant associations were observed at the other ages. Conclusions: Intake of added sugars and fructose increased precipitously over the first 2 years of life and added sugars intake was well above the recommended 0 grams/day for children < 2 years of age. Analyses suggested a qualitative transition in intake occurring for both forms of sugars toward the end of the first year. Timing of intake in the first 1, 000 days of life, along with the form of sugar consumed, may impact child body composition differently. Funding Sources: The KUDOS study was supported by US NIH grants R01HD047315 and U54 HD090216.